The International Control Conundrum: The Case of ‘Hyperinflationary’ Subsidiaries - Jacque, Laurent L.; Lorange, Peter (Journal of International Business Studies, 1984)
Standard methods for financial controls of multinational corporations' (MNCs) foreign subsidiaries generally provide inadequate managerial support under conditions of extreme environmental turbulence, resulting in a highly distortive performance evaluation system. This article examines the specific conditions of monetary hyperinflation and how existing control systems should be upgraded or environmentalized in order to cope with such operating conditions. A taxonomy of hyperinflationary environments and a control model—based upon variance analysis—aimed at smoothing excessive swings in the performance of foreign operations is developed, thereby correcting for some of the dysfunctionalities in the traditional planning and control processes.